Prediction of the Flow-Induced Vibration Response of the Chenderoh Dam Left Bank Section - Ghazali M.H.M.; Zawawi M.H.; Hassan N.H.; Radzi M.R.M.; Mazlan A.Z.A.; Abas M.A.; Zainol M.R.R.M.A. (EDP Sciences, 2023)
Dams; Disaster prevention; Frequency domain analysis; Natural frequencies; Resonance; System theory; Vibrations (mechanical); Dam structure; Flow induced vibrations; Frequency domain response; Natural frequencies and modes; Operational conditions; Operational deflection shapes; Resonance phenomena; Transient vibration response; Rivers